Window from within: Investigating an architectural element through designing an artist studio collective - Johansson, Stina (My University, 2021)
What is a window and what does it do? This thesis aims to explore the window as a functional device from an interior perspective when situated in a certain program. The main question is how the form, placement and functionality of the window affect the sensation of an interior space. A window is not inseparable from a house; whereas walls, floor and roof might be the essentials of a shelter, windows are not fundamentally necessary for protection. However architecture is more than protection and in a society where we spend a big part of our days indoors light intake and visual connection with the world outside affects our wellbeing. Dense cities are challenging the admission of day light into buildings and visual connections ought to be planned with integrity in mind. On a stylistic level though; is it possible to separate the window from the house, the detail from the whole? Windows can be controversial and provocing and has been a source of conflict between architects and in society. Whether essential to create a space or not; the window contributes to the sense of space. It is a connection between two spaces, an interface between interior and exterior through admission of light, wind and view. Looking it up in a dictionary it can even be explained as a space in its own right. This thesis will be carried out through reading, making case studies, making site mapping and trying out different shapes and placements of windows digitally as well as in physical model. The aim is to find a design proposal for a studio collective for painters at an urban site, using this as a vehicle for learning about window design.
Keywords: Houses, roads, skies, blue coastal inlets, mountains, opened their windows